2013
DOI: 10.1002/ps.3612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of emamectin benzoate and propiconazole for protecting individual Pinus contorta from mortality attributed to colonization by Dendroctonus ponderosae and associated fungi

Abstract: Previous evaluations of emamectin benzoate for protecting P. contorta from mortality attributed to D. ponderosae have failed to demonstrate efficacy, which was later attributed to inadequate distribution of emamectin benzoate following injections applied several weeks before D. ponderosae colonization. The present data indicate that injections of emamectin benzoate applied in late summer or early fall will provide adequate levels of tree protection the following summer, and that, when emamectin benzoate is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Unfortunately, the effectiveness of some of these direct management approaches (sanitation, insecticide, semiochemicals) does not last more than 2 years, some have a negative effect on the environment (insecticide), and some require higher cost, skills, and labour (sanitation, prescribed fire) to implement [26,[28][29][30]. Thus, with the high intensity of attack, management efforts were eventually shifted to salvage logging (clear cut) operations to capture as much of the economic value of dead timber as possible before the wood deteriorated and may slow the spread of beetles to other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the effectiveness of some of these direct management approaches (sanitation, insecticide, semiochemicals) does not last more than 2 years, some have a negative effect on the environment (insecticide), and some require higher cost, skills, and labour (sanitation, prescribed fire) to implement [26,[28][29][30]. Thus, with the high intensity of attack, management efforts were eventually shifted to salvage logging (clear cut) operations to capture as much of the economic value of dead timber as possible before the wood deteriorated and may slow the spread of beetles to other areas.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some previous studies have stated that pesticide combinations (insecticides and fungicides) are usually more effective than only fungicide or insecticide applications for controlling ambrosia beetles and symbiotic fungi in the field (Fettig et al, 2014;Ranger et al, 2016;Jones et al, 2017). Fettig et al (2014) determined that pesticide combinations [emamectin benzoate (insecticide) and propiconazole (fungicide)] injected with arborjet was more effective than single pesticide treatments for protecting pine trees from bark beetle, Dendroctonus ponderosae Hopkins (Scolytinae). Jones et al (2017) found that the combination of a systemic insecticide (emamectin benzoate), a contact insecticide (bifenthrin), and a fungicide (metconazole) provided the best control against ambrosia beetle, Euwallacea sp.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that azoxystrobin, iprodione and thiram inhibited the mycelial growth of the symbiotic fungus at the rates of 50-85%, 65-100% and 75-100% depending on increased doses, respectively. However, in a few studies, some researchers tested the effects of fungicides to symbiotic fungi associated with ambrosia beetles in field conditions (Mayfield et al, 2008;Fettig et al, 2014;Ranger et al, 2016;Jones et al, 2017). Mayfield et al (2008) found that propiconazole, which was enjected into redbay (Persea borbonia) trees, inhibited the growth of Raffaelea sp.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of significant advancement in MPB management, none of this knowledge can solely mitigate the problem and management still depends on sanitation harvesting to control infestations by removing infested trees, use of prescribe fire, insecticides (MSMA), semiochemicals, or pheromones used on trap trees (Coops et al 2008;Fettig et al 2014;. Unfortunately, the effectiveness of some of these direct management approaches D r a f t (sanitation, insecticide, semiochemicals) won't last more than 2 years, some have a negative effect on the environment (insecticide), and some require higher cost, skills, and labour (sanitation, prescribed fire) to implement (Fettig et al 2007;Coops et al 2008;Wulder 2009;Fettig et al 2013b;Gillette et al 2014;Progar et al 2014). On the other hand, some researchers suggest indirect management or pre-emptive logging in advance of beetle infestation, such as thinning from below, tree crown thinning, and selection thinning treatments (Dahlsten and Rowney 1983;Mitchell et al1983;Fettig et al 2007).…”
Section: Management Of Mpb Outbreaksmentioning
confidence: 99%